1995
DOI: 10.1007/bf02311173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuropeptide Y, insulin, 2-deoxyglucose, and food deprivation on food-motivated behavior

Abstract: The current study demonstrates the ability of neuropeptide Y (NPY) to increase break points under a progressive ratio 1 (PR1) reinforcement schedule. An initial response resulted in delivery of a food reinforcer (45 mg pellet) under the PR1, and an additional response was required for each successive reinforcer. The break point, the number of responses emitted to obtain the last reinforcer, is considered a measure of reinforcing efficacy or motivational strength of the food reinforcer. NPY (0.3-10 micrograms) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 24 publications
7
47
1
Order By: Relevance
“…In contrast, we found that peripheral administration of the anorectic hormone leptin significantly decreases breakpoints for HFHS food in mice. These findings are consistent with previously reported actions of food deprivation and leptin on reward thresholds in rats [12][13][14] . When using this protocol it is important to keep in mind that acquisition of food-maintained operant responding is significantly enhanced by regular training (every 1-2 days) and by increasing the motivational state of the mouse by implementing a food restriction regimen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, we found that peripheral administration of the anorectic hormone leptin significantly decreases breakpoints for HFHS food in mice. These findings are consistent with previously reported actions of food deprivation and leptin on reward thresholds in rats [12][13][14] . When using this protocol it is important to keep in mind that acquisition of food-maintained operant responding is significantly enhanced by regular training (every 1-2 days) and by increasing the motivational state of the mouse by implementing a food restriction regimen.…”
Section: Discussionsupporting
confidence: 93%
“…For example, depleting utilizable glucose by peripheral 2-deoxyglucose administration in rats increases the amount of freely available food consumed but fails to alter break points in a PR task for food 12 . PR breakpoint responding can also reflect changes in the quality of food rewards.…”
Section: Discussionmentioning
confidence: 99%
“…As expected (Hodos, 1961, Jewett et al, 1995 food restriction prominently increased operant responses for sucrose ( Figure 3A vs. Figure 1A for satiated responses). This effect was ablated by administration of JMV2959.…”
Section: Vta Jmv2959 Microinjectionsupporting
confidence: 80%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 19 While the importance of ghrelin in reward-motivated feeding is now strongly supported, and here we have indicated the VTA as a ghrelin-responsive neuroanatomical substrate underpinning motivated food reward behavior, it is possible that there are additional anatomical loci underlying these responses. In the arcuate nucleus ghrelin signaling stimulates the activity of NPY/AgRP neurons (Dickson et al, 1993, Kamegai et al, 2001) and, in lateral hypothalamus, the orexin neurons (Toshinai et al, 2003); orexin, NPY and AgRP have some role in reward behavior (Jewett et al, 1995, Tracy et al, 2008a, Cason et al, 2010 and therefore these cannot be excluded as an additional target site(s) of ghrelin that mediate some effects of ghrelin on the mesolimbic circuitry in addition to the direct effect of ghrelin on the mesolimbic circuit shown here.…”
Section: Discussionmentioning
confidence: 80%
“…Self-stimulation within certain lateral hypothalamic sites induces an eating response, and selfstimulation-induced feeding is augmented with food restriction (15). Likewise, the ability of food to condition a place preference, or self-administration of food, is increased with food deprivation (16)(17)(18)(19)(20). Since peripherally-derived signals of body adiposity or energy homeostasis, i.e., the pancreatic hormone insulin and the adipose-derived hormone leptin, have been shown to act within the CNS (21), their role in mediating the effect of food restriction on motivational behaviors has been investigated (1).…”
Section: Introductionmentioning
confidence: 99%